Dilema Pewarisan Data Digital untuk Pengembangan Pendidikan Indonesia: Perspektif tentang Forensik, Etika, dan Hukum Privasi - Alisya, Namirah; Rindy, Rindy; Wahyumi, Aida; Wibowo, Wahyu Catur; Orvin, Timothy (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The transition to the digital age has transformed the concept of inheritance, as non-financial digital assets now hold significant emotional and personal value; however, access to such data has sparked a conflict between post-mortem privacy rights and the legitimate access needs of heirs. This study finds that Indonesia’s 2022 Personal Data Protection Act (PDP Act) contains a serious legal vacuum because it only protects living data subjects—a gap exacerbated by the internal policies of global service providers that often block heirs’ access. Drawing on the work of Luciano Floridi, this study emphasizes the importance of the state’s role as Steward of the Infosphere to prevent “Information Entropy” resulting from unmanaged data. As a solution, this study proposes a three-pillar framework encompassing legal reform through data classification and the legal recognition of Digital Trustees, standardization of forensic procedures based on the Philosophical Model of Forensic Decision-Making (MPKF) aligned with ISO/IEC 27037, and institutional strengthening through notarial protocols and Supreme Court regulations. The integration of these three aspects aims to fill regulatory gaps, ensure legal certainty, and protect the rights of heirs amidst the complexity of digital technology in Indonesia